EZH2 promotes proliferation and invasiveness of prostate cancer cells. - Bryant, R; Cross, N; Eaton, C; Hamdy, F; Cunliffe, V (2007)
BACKGROUND: The transcriptional repressor EZH2 is implicated in control of cell proliferation in embryonic, immortalized and transformed cells. EZH2 expression in prostate cancer correlates with progression to hormone-refractory and metastatic disease, but it is unknown whether EZH2 plays a specific role in the acquisition of an advanced prostate cancer phenotype. METHODS: Using siRNA knockdown, we investigated the role of EZH2 in maintenance of prostate cancer cell proliferation and invasiveness. Using LNCaP cells with inducible EZH2 overexpression, we investigated whether EZH2 upregulation promotes an aggressive phenotype. RESULTS: Knockdown of endogenous EZH2 reduced proliferation of androgen-responsive and androgen-independent prostate cancer cells. EZH2 knockdown also inhibited prostate cancer cell invasion. However, overexpression of EZH2 in androgen-responsive cancer cells did not appreciably affect either proliferation or invasiveness. CONCLUSIONS: EZH2 promotes proliferation and invasion of prostate cancer cells, which can account for the correlation between EZH2 expression levels and an adverse prostate cancer prognosis.